Wymagania wobec prowadzących księgi rachunkowe w regulacjach polskich i międzynarodowych - Zuchewicz, Joanna (Requirements regarding persons responsible for running account books in Polish and international regulations, 2007)
In Poland the issues related to providing services consisting in running account books are regulated by the following laws: 1. the Act dated 13 October 1994 on expert auditors and their authorities, 2. the Act dated 5 July 1996 on tax consultancy, 3. the Minister of Finance Regulation dated 18 July 2002 regarding the entitlement for providing services consisting in running account books. In accordance with the above legal acts individuals entitled to provide services of running account books are as follows: expert auditors, tax consultants and individual persons certified as public accountants. Account books may also be run by persons employed on the basis of work contract at the position of an accountant. For this particular group of people International Education Standards for Professional Accountants were addressed. They entered into force on I January 2005 and were elaborated by the IFAC Committee for Education with an official seat in New York. International Education Standards are not observed as legal regulations and they do not overrule national legislation, however, they point to the direction which particular state regulations should follow.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 197-211